Art Criticism and Gender - de la Villa Ardura, Rocío (Investigaciones Feministas (Feminist Research), 2013)
Gendered art criticism shorts the gap with audiences. This status of the issue paper analyzes through eleven proposals four concentric circles: renovation of art historiography; erosion of canon and neutral criteria; gender infiltration on contemporary art criticism; and the estate of feminist criticism at present.